Proportion of Outpatient’s Perception in Srinagarind Hospital about Drugs after Receiving from Central Dispensary - Kongtong, Theerakarn; Saengmongkonpipat, Pattawee; Jeerasuwannakul, Weerin; Suwanchai, Kanta; Khongsaenkham, Rungthiwa; Kuhirunyaratn, Piyathida; Ratanasiri, Amornrat (Srinagarind Medical Journal, 2016)
Background and Objective: Although drugs are important factors affecting the treatment ,There are a few people that have a right perception to their drug. So, Knowing amount of right perception people is important. This study aimed to find the proportion of outpatient’s perception of drugs and factors that affected the perception. Method: This descriptive study studied population as outpatients getting drugs from central dispensary of Srinagarind hospital. Time allocation random samples of 143 patients were interviewed with oral questionnaire. Result: From interviewing 143 unit, there were 143 responds (100% of interview). There were 44 males (30.8%) and 99 females(69.2%).Patients’ age was 18 to 84 year-old (median 56 , IQR 18 ). Most of the patients’ education was bachelor degree or higher, 57 patients (39.9%). There were 53.85 % of patient with right drug perception (95% CI: 45.34, 62.15), 77.62 % of patient with right drug purpose (95%CI: 69.74, 83.98), 72.72 % of patient with right dose of drug per time (95%CI: 64.54, 79.67) and 61.54 % of patient with right time to intake the drug ( 95%CI: 53.01, 69.44). Data analysis, by multiple logistic regression, expects that right drug perception related to amount of drug and type of receiving drug (old or new drug) p <0.0001, adjusted OR 0.71 (95%CI 0.58 , 0.87) and 0.19 (95% CI: 0.91, 0.38). Conclusion: Half of the patients had right drug perception. Factors that associated with drug perception were increasing amount of drugs and receiving new drugs. These factors decreased drug perception.